Health and the Second Spanish Republic (1931-1936): the creation of the figure of the first Head of Nurses - Francisco Javier Castro Molina; Natalia Rodríguez-Novo; Felisa-Vanessa (Universidad de Alicante, 2017)
Introduction: Healthcare in Spain, as in many other countries, was a top concern for their ruler. But it is during the Second Spanish Republic (1931-1936) when this restlessness becomes more alive. To improve it was allocated a budget that, after exercise, was increased to solve the serious problems that suffered, seeking only the modernization of existing infrastructures and the creation of so many new ones, in addition to achieving a maximum qualification of its professionals. This last one was of considerable draft, matching it with the flamboyant examples of many other European countries that bet on leaving behind models anchored in the Middle Ages and giving way to a system that functions as a "healing machine". Objective: Establish when the figure of the Director of Nurses emerges for the first time in Spain. Method: A "thorough examination" of the documentation was carried out in the Archive of the Very Insular Cabildo of Santa Cruz de Tenerife and bibliographically. Results: In the Canary Islands, as in many other places in the "bullskin", the reforms were pursued deep. A clear example of this was the regulation, of short time in force, formulated by the councilor of the Insular Cabildo of Tenerife Miguel Bethencourt of the River, that gave a turn to the existing organization until that moment. Conclusions: Among the changes highlighted the creation of the figure of Director of Nurses, unpublished until now, and that we had to wait for the sunset of the Franco dictatorship to see it again in the Spanish Health.